Overview of Homestead Farming - Coconut in Kerala - Gadhe, Shruthi; Mathur, Aditi (International Journal of Bio-resource and Stress Management, 2018)
Coconut is a crop which is cultivated mostly by the people of tropical countries where the water facility is abundant as the crop requires more amount of water for its growth. Coconut is considered as the “tree of life” in developing countries as they depend on it as a source of food, medicine, shelter, fuel and furniture among others. Coconut is considered as one of the most important cash crop throughout the world. Coconut is an age old crop cultivated more in the tropical countries. India consists of a vast line of coastal region which is suitable for growth of coconut and it is cultivated around 13 states covering the area of 2.09 mha. Coconut cultivated in Kerala is of 8.2 Lakh ha which occupies 38% of net cropped area and provides livelihood to over 3.5 million families in Kerala. This paper is based on the secondary data and attempt is made to find out the share of coconut cultivation and production in Kerala. The trend is also shown for area and production from the year 2000-01 to 2015-16 and analyzed the growth rates of area, production and productivity which resulted in negative growth rate which indicates in the decrease of coconut cultivation which is a main homestead crop in Kerala. The index number revealed the area, production and productivity of coconut in each year.